An analysis on the preliminary benefits of aquaculture smart aeration control. Issue 1 (19th November 2022) - Lin, Chi‐Yuan; Shen, Yu‐Tang; Tsai, Yong‐An; Chen, Chao‐Chien
Abstract: Aquaculture in Taiwan is characterised by high breeding densities of up to five times higher than the normal breeding densities. Pollution in the breeding environment and its adjacent waters have exacerbated the occurrence of disease outbreaks in fish, shrimp and shellfish, which greatly impacted the economy. Therefore, the parameters pertaining to water quality status, especially dissolved oxygen are particularly important. In addition to the rising cost of labour, land, infrastructure and other materials, the capital needed to engage in aquaculture has risen, whereas the profits have decreased. This limits the growth of aquaculture and fisheries. To overcome this problem, it is essential to shift towards efficient and ecologically precise smart aquaculture. The application of industrialised and smart systems in the vertical diffusion and in‐depth integration of aquaculture facilitates decision‐making, improves the level of intelligence in breeding, and enhance aquaculture's contribution to Taiwan's economy. Abstract : The preliminary analysis results have confirmed that the smart aeration control system can instantly identify signal anomalies and trigger field equipment regulations depending on the varied degrees of anomaly andcould maintain field water quality stability by using less energy and manpower costs.